Sarcopenia evaluated by phase angle is associated with complications and mortality Pre- and Post-Liver Transplantation - Atzin M. Melchor-Zepeda; Mariana López-Caracas; Andrea Reyna-Sariñana; Renata S. Montemayor-Salazar; Luis E. Gutierrez Rosas; Berenice M. Román-Calleja; Ricardo U. Macías Rodriguez; Astrid Ruiz-Margáin (Annals of Hepatology)
Introduction and Objectives: Sarcopenia is a marker of poor prognosis in patients with cirrhosis. Evidence on the role of sarcopenia prior to liver transplantation (LT) and its impact on post-transplant outcomes remains limited. Phase Angle (PhA) is a nutritional marker that has been validated against CT scan for assessing sarcopenia in cirrhosis. We aimed to evaluate the association between phase angle and the development of complications and mortality before and after liver transplantation. Materials and Patients: This was a retrospective cohort study conducted at a tertiary care center. Patients with cirrhosis of any etiology, being evaluated for liver transplant that had a phase angle measurement before LT were included. We excluded patients that were considered for LT for causes different from cirrhosis (polycystic liver disease, benign bile duct injury, acute liver failure, etc.). For statistical analysis descriptive statistics were used, along with ROC curves and Youden index, Kaplan-Meier survival analysis and Cox regression models were also applied. Results: A total of 141 patients were included in the study, of which 55% were women, with a mean age of 53 ± 13 years. Mean phase angle was 4.5 ± 2.1, and the mean MELD Na score was 17 ± 7; most patients (45.4%) were classified as Child-Pugh C stage. The median follow-up period was 224 days (range 83-301). At least one hospitalization was required for 49.1% of patients, with a waiting list mortality rate of 35.7%, primarily due to septic shock (36.3%). Post liver transplant mortality was 13.8%. Complications were observed in 65.5% of patients, predominantly infections (25%). ROC curves indicated that a PhA < 3.8° was associated to an increased risk of hospitalization and infectious complications both before and after LT, with Area Under the Curve (AUC) values of 0.703, 0.683, and 0.704, respectively (p < 0.001). Kaplan-Meier survival analysis showed better outcomes for patients with PhA > 3.8° (p = 0.001). Two multivariate models were developed to account for collinearity: in both, a lower PhA <3.8° was associated with a higher mortality risk, with Hazard Ratios (HR) of 1.98 (1.02-3.84) and 2.01 (1.02-3.94), independent of MELD score and Child-Pugh stage, respectively. Conclusions: Sarcopenia, assessed by phase angle, is associated with complications before and after liver transplantation, particularly infections, higher number of hospitalizations, and increased mortality.